Grassroots Community Music Education as a Strategy for Liberating Marginalized Communities in Surabaya - Bayu Aji Wicaksono; Warih Handayaningrum; Setyo Yanuartuti (Gondang: Jurnal Seni dan Budaya, 2025)
This article discusses community music education as social emancipation for marginalized groups in Surabaya based on a case study of POSS (Surabaya Arts Center). For the sake of this research, POSS was explored qualitatively using a case study approach. The data were collected using interviews, observation, and documentation. The study demonstrates that POSS assumes Freire's pedagogy of the oppressed by embracing dialogic, participatory, and experiential education as principles of education. Music education at POSS is geared not just towards technical proficiency but also towards self-discovery, social identity transformation, and active citizenship of students in public life. A few of the students have proceeded to perform nationally and internationally and establish identical art communities in other regions of the country. These results illustrate that music education via community can effectively facilitate social mobility and new spheres of representation for marginalized groups. Furthermore, the study highlights the imperative of cultural recognition, trust-based leadership, and inclusive pedagogy in transforming how education can reach out to underserved communities. POSS demonstrates that music education has the potential to transform not only individuals but also communities, when it is founded upon lived experience and collective empowerment. This research calls for stronger support for community-based arts education as a genuine commitment to social justice and cultural inclusion in the educational system of Indonesia.